THE RELATIONSHIP BETWEEN CEREBROSPINAL FLUID PRESSURE AND ATHEROGENIC INDEX OF PLASMA IN IDIOPATIC INTRACRANIAL HYPERTENSION PATIENTS - Şimşek, Fatma; Yevgi, Recep; Dağcı, Yıldız (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2022)
Background: Idiopathic intracranial hypertension (IIH) is a disease thought to be associated with obesity and rapid weight gain. There is no objective parameter with practical use in its follow-up and treatment other than optical coherence tomography.Objective: The aim of our study is to investigate the relationship between atherogenic index of plasma (AIP) and cerebrospinal fluid (CSF) pressure.Methods: Serum vitamin B12, vitamin D, homocysteine, folic acid, triglyceride (TG), high density lipoprotein cholesterol (HDL-C) levels, CSF pressure, CSF microprotein levels were recorded from the file data of patients diagnosed with IIH. AIP was calculated by dividing the TG level logarithmically by HDL-C. Height (kg) and weight (kg) data of the patients were used to calculate the body mass index (BMI).Results: File data of 64 patients were examined. 8 patients with secondary intracranial hypertension were excluded from the study. 80.36% of the patients were overweight, 16.07% were obese, 3.57% were with normal weight. There was no significant correlation between vitamin B12, vitamin D, homocysteine, HDL-C and CSF microprotein levels and CSF pressure level in patients with a diagnosis of IIH. There was a negative correlation between folic acid level and CSF pressure level, and a positive correlation between BMI, TG, AIP and CSF pressure level.Conclusion: Using folic acid supplements and drugs that reduce TG levels can contribute positively to the course of the disease.